Pengaruh Teknik Tracing the Dots terhadap Kemampuan Menulis Huruf Vokal pada Anak Disabilitas Intelektual Sedang Kelas II - Fata, Khairul Alvin Hadi; Prystiananta, Nostalgianti Citra; Nurhadiyati, Arifah (JOEAI (Journal of Education and Instruction), 2025)
This study aims to determine the effect of the Tracing the Dots technique on the vowel writing ability of second-grade students with moderate intellectual disabilities at the BCD YPAC Jember Special Needs School. The method used was a quantitative one-group pretest-posttest design. The results showed that the calculated Z value (4.91) was greater than Zα (1.645); thus, H₀ was rejected and Hₐ was accepted. This means that the application of the Tracing the Dots technique has a significant influence on the vowel writing ability of second-grade students with moderate intellectual disabilities at the BCD YPAC Jember Special Needs School. The conclusion is that the Tracing the Dots technique is efficacious in improving vowel writing ability in children with moderate intellectual disabilities. Therefore, this technique can be used as an alternative writing learning strategy for teachers in special needs schools.   Keywords: Intellectual Disability, Vowel Writing, Tracing the Dots Technique